Diversões e civilidade na “Princesa do Sertão” (1919-1946) - Santos, Aline Aguiar Cerqueira dos (2012)
Analyze some of the amusements and forms of sociability in Feira de Santana, in the period 1919 to 1946 in its relations with the discourses of progress and civility proposal to the city, emphasizing especially the role of Cine-Teatro Santana. Thus, we emphasize this playhouse, because it is a multifunctional space in which diverse experiences and social practices, cultural and policies were developed, enabling us to understand a facet of everyday life feirense. Among the entertainments we have analyzed here: the philharmonic, the literary-dramatic guilds, football, circus, theater and cinema. Many groups linked diversions mentioned above somehow gravitated around the Cine-Teatro Santana, promoting shows in support of various charitable institutions of the city, thereby establishing a network of solidarity between cultural assnociations and charitable institutions.